2019
DOI: 10.1186/s12884-019-2369-5
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of overuse? Patterns of obstetric interventions during labour and birth among Australian mothers

Abstract: Background There is global concern for the overuse of obstetric interventions during labour and birth. Of particular concern is the increasing amount of mothers and babies experiencing morbidity and mortality associated with caesarean section compared to vaginal birth. In high-income settings, emerging evidence suggests that overuse of obstetric intervention is more prevalent among wealthier mothers with no medical need of it. In Australia, the rates of caesarean section and other obstetric interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 43 publications
(54 reference statements)
2
18
0
Order By: Relevance
“…The fact that nearly half of all records did not report on labour onset (and thus labour length) was unexpected, the consequences of which are seen in the large discrepancy between recall and actual events for this variable. This is a critical omission, as length of labour is an important trigger for routine labour interventions [38] . Moreover, it limited our ability to assess the level of agreement with precision.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that nearly half of all records did not report on labour onset (and thus labour length) was unexpected, the consequences of which are seen in the large discrepancy between recall and actual events for this variable. This is a critical omission, as length of labour is an important trigger for routine labour interventions [38] . Moreover, it limited our ability to assess the level of agreement with precision.…”
Section: Discussionmentioning
confidence: 99%
“…35 36 Concerns have been raised in many studies about the increasing trend of multiple pregnancy reported both in China and worldwide, which was associated with the global rise in advanced maternal age, infertility treatments and obstetric interventions performed before 37 gestational weeks, especially at 34-36 weeks. [37][38][39][40][41] on November 1, 2020 by guest. Protected by copyright.…”
Section: Discussionmentioning
confidence: 99%
“…This contrasted with higher use of inpatient contacts in the other large cities with similar risk profiles. The time period of the present analysis included decreasing mortality in healthy Danish children, and steady total use but increased specialisation of health services [5,8,9]. Thus, a focused comparison of the organisation of the health system responsible for referral and admission of ill, but basically healthy children in the four major urban areas in Denmark could be useful: perhaps Copenhagen admit too many children or, alternatively, Aarhus admit too few.…”
Section: Plos Onementioning
confidence: 99%
“…However, socioeconomic inequalities in child mortality persist between and within countries [2,3]. Denmark is a high-income country, but even in the Danish setting inequality may be present despite free access to health services, since more resourceful citizens may be better at seeking health services, or the health care system may not prioritise according to the need of the citizens [4][5][6].…”
Section: Introductionmentioning
confidence: 99%